Techniques to inhibit transformer insulating oil degradation - Effectiveness evaluation of the removal of degradation products using adsorbents - Wada, Junichi; Ueta, Genyo; Okabe, Shigemitsu; Amimoto, Tsuyoshi (IEEE transactions on dielectrics and electrical insulation, 2013)
For long-term operation of power transformers, as well as ensuring their insulating reliability, an adequate study must be conducted on the age-related decline in various insulating oil characteristics and the method to inhibit the decline. In the present paper, to inhibit the degradation of insulating oil, a study was conducted on a method of removing the degradation products generated in insulating oil due to aging and the effect of removing these products. Consequently, for simulated degraded oil subjected to heat stress of 10 years old, degraded through the accelerated degradation of new oil, the performance of insulating oil subject to such accelerated degradation was improved through adsorption treatment and short-term improvement was able to be observed. Following reheating after the adsorbent treatment, a long-term improvement effect to prevent the decline in insulating oil characteristics due to degradation was able to also be observed. On the other hand, for the insulating oil aged about 30 years in the field, the effect was less than that for simulated degraded oil equivalent to about 10 years old. The effect of the adsorbent was able to vary depending on the amount used and the degree of insulating oil degradation. Accordingly, volume resistivity, representing the degree of insulating oil degradation, was varied to study the effect of the adsorbent with respect to its amount. As a result, it emerged that, as the amount of adsorbent was increased, the inhibitory effect on degradation increased but the effect was less significant for insulating oil with volume resistivity significantly decreased. Based on these results, it was clarified that, for aged oil with a low degree of degradation, an inhibitory effect on the short- and long-term decline in insulating oil characteristics was able to be obtained through adsorbent treatment.